Study of Fish Exploitation Pattern of River Bharathapuzha, Kerala, India - Renjithkumar, C. R.; Roshni, K.; Kurup, B. M. (Fishery Technology, 2021)
A total of 31 finfish species belonging to 7 orders and28 genera and one shell fish species were recordedin the exploited pattern of Bharathapuzha river. Totalannual fish landing from the Bharathapuzha riverwas quantified as 112.56 t. Highest landing wasrecorded during the post-monsoon season andlowest during the monsoon season. The main speciescontributed to the landing are Dawkinsia filamentosa(17.34 t), Systomus sarana (12.06 t), Hypselobarbuskurali (9.89 t), Parambassis dayi (8.39 t) and Wallagoattu (7.61). Gibelion catla, Labeo rohita, Cirrhinusmrigala (Indian major carps) and Oreochromismossambicus were the non-native species representedin the exploited fishery. Gill nets, cast nets, seine netsand hook and lines were the major fishing gears usedin the river. Catch per unit effort (CPUE) recordedin gill net for major species were Pseudetroplusmaculatus (0.75 kg h-1), Devario aequipinnatus (0.5 kgh-1), L. rohita (0.38 kg h-1), D. filamentosa (0.20 kgh-1) and S. sarana (0.18 kg h-1). The highest CPUErecorded in cast net was for Hypselobarbus kurali (0.51kg h-1), Hyporhamphus xanthopterus (0.50 kg h-1),Mystus vittatus (0.38 kg h-1) and W. attu (0.29 kgh-1). In seine net high CPUE was recorded in Channastriata (0.17 kg h-1), L. rohita (0.16 kg h-1) and Etroplussuratensis (0.13 kg h-1).